Eating disorder risk and pathogenic behaviors among collegiate student-athletes - Torres-McGehee, T. M.; Uriegas, N. A.; Hauge, M.; Monsma, E. V.; Emerson, D. M.; Smith, A. B. (Journal of Athletic Training, 2023)
Key Points